Identifying pain trajectories in children and youth with cerebral palsy: a pilot study - Heather M. Shearer; Pierre Côté; Sheilah Hogg-Johnson; Patricia McKeever; Darcy L. Fehlings (BMC, 2021)
Abstract Background Although chronic pain is common in children with cerebral palsy (CP), little is known about short-term pain fluctuations and their impact on children's well-being. High-quality cohort studies are needed to understand the clinical course of pain in this population. We aimed to determine the feasibility of conducting a multicentre cohort study. In this pilot study we assessed: 1) study processes, 2) resource and 3) management indicators including recruitment and follow-up rates, data completeness, participant characteristics, and successes and barriers in the study conduct. Methods A multi-centre pilot cohort study was conducted with 10 Canadian children/youth with CP attending one of two children's rehabilitation centers. We collected self-reported pain intensity (Faces Pain Scale-Revised [FPS-R], Numeric Rating Scale [NRS]); pain interference (PROMIS PI); pain location (pain diagram); physical and psychological well-being (KIDSCREEN-27), sleep characteristics, preceding months' interventions, and some clinical characteristics at baseline. Average pain intensity was reported weekly for five weeks. Well-being, sleep and interventions were measured at baseline and again at five weeks. We used feasibility indicators to evaluate:1) study processes (e.g. recruitment, attrition rates); 2) resources (e.g. data completion, budgetary challenges); and 3) management (e.g. data optimization, variability of participants and pain scores). Results Between March and May 2019, 24 children and their parents/guardians were contacted and 20 met eligibility criteria. Of those, 10 agreed to in-person screening (50%) and were subsequently enrolled. The follow-up rate was 90% and self-reported missing data was minimal. Ninety percent of participants chose e-questionnaire follow-ups versus mailed paper questionnaires. Sixty percent required reminders to complete e-follow-ups. Participants were aged 8-17 years, five were female, GMFCS levels I-IV (none with level V), 90% had spastic CP and 80% reported having pain in the preceding week. Pain intensity (FPS-R) between participants ranged from 0-8/10 at baseline and 0-6/10 across all four weekly follow-ups. Conclusions This pilot study demonstrates the feasibility of conducting a multicentre cohort study to identify short-term pain trajectories and measure their association with well-being in children and youth with CP. Additional strategies to improve recruitment and accessibility for those with GMFCS levels V should be implemented in future studies.